Semaforización en la atención en salud en la Fundación Casalud (2022)
The Casalud de Monteria Foundation is a company that transforms lives, through education, prevention, protection and specialized treatment programs that allow the social inclusion of people in the different areas of human development. The following work shows a project that consists of the management of a database in Excel using macros of the same as an application to efficiently signalize the dates of preparation and presentation of the documents of each area of the Casalud Foundation such as psychology, social work, pedagogy, health and nutrition.